Magnetically Enhanced Liquid SERS for Ultrasensitive Analysis of Bacterial and SARS-CoV-2 Biomarkers - Ji, Zhang; Zhang, Chuan; Ye, Yang; Ji, Jiali; Dong, Hongguang; Forsberg, Erik; Cheng, Xiaoyu; He, Sailing (Frontiers in Bioengineering and Biotechnology, 2021)
In this work, it is shown that Surface-enhanced Raman scattering (SERS) measurements can be performed using liquid platforms to perform bioanalysis at sub-pM concentrations. Using magnetic enrichment with gold coated magnetic nanoparticles, the high sensitivity was verified with nucleic acid and protein targets . The former was performed with a DNA fragment associated with the bacteria Staphylococcus aureus, and latter using IgG antibody, a biomarker for COVID-19 screening. It is anticipated that this work will inspire studies on ultrasensitive SERS analysers suitable for large scale applications, which is particularly important for in vitro diagnostics and environmental studies.